SiO2/Au core-shell nanoparticles: synthesis and characterization - Matveevskaya, N.A.; Tolmachev, A.V.; Pazura, Yu.I.; Savvin, Yu.N.; Dukarov, S.V.; Semynozhenko, V.P. (STC “Institute for Single Crystals”, 2005)
Preparation of heteronanoparticles of the core-shell type has been described based on single-dispersed spherical nanoparticles of silicon dioxide and gold. Using the colloid chemistry techniques, nanoparticles having different dielectric core diameters and different metal shell thickness have been obtained. The effect of the nanoparticle structure on the absorption spectra thereof has been investigated. The maximum position in the absorption spectra has been shown to be defined by dielectric core diameter ratio to the gold shell thickness in the SiO2/Au nanoparticles. - - - - - - - - - - - Приведены результаты по получению гетеронаночастиц типа "ядро-оболочка" на основе монодисперсных сферической формы наночастиц диоксида кремния и металлического золота. Методами коллоидной химии получены наночастицы с различным диаметром диэлектрического ядра и толщиной металлической оболочки. Изучено влияние структуры наночастиц на спектры поглощения. Показано, что отношение диаметра диэлектрического ядра к толщине золотой оболочки определяет положение максимума в спектрах поглощения гетеронаночастиц SiO2/Au. - - - - - - - - - - - Наведено результати з одержання гетеронаночастинок типу "ядро-оболонка" на основі монодисперсних сферичної форми наночастинок діоксиду кремнію та металевого золота. Методами колоїдної хімії одержано наночастинки з різним діаметром діелектричного ядра і товщиною металевої оболонки. Вивчено вплив структури наночастинок на спектри поглинання. Показано, що відношення діаметра діелектричного ядра до товщини золотої оболонки визначає положення максимуму в спектрах поглинання гетеронаночастинок SiO2/Au.
Keywords: Thin films; nanoparticles